THE DIGITAL GATEWAY: HARNESSING FINTECH FOR SME DEVELOPMENT IN UZBEKISTAN'S TRANSITION ECONOMY - Nurmuhammedova Barno Ismailovna,; Rakhimboyeva Sugdiyona Rakhimboyevna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation:  The  article  examines  the  influence  of  digital  financing  on entrepreneurship and SME development in Uzbekistan’s evolving digital economy. It highlights how initiatives such as the “Digital Uzbekistan 2030” Strategy and the rise of  super-app  platforms  have  expanded  financial  inclusion  and  accelerated  cashless transactions.  At  the  same  time,  the  study  notes  ongoing  barriers  to  SME  growth, including strict collateral requirements, limited financial literacy, cyber risks, and rural connectivity gaps. The paper emphasizes the need to strengthen alternative financing regulations  and  invest  in  digital  skills  and  security  to  support  inclusive  economic development.